(untitled) (Genius Repository, 2023)
In this article, the Kafirkala monument, which made an important contribution to the development of the Central Sugdian statehood on the Great Silk Road , and the receptions and ceremonies of this monument , which were not just an ordinary residence of the rulers of Samarkand at the end of the 7th century, but had a special national significance here. and revealed to have been an important residence where ceremonies were held.